Seminoma with atypical features: Implications of a distinct disease entity (Indian Journal of Case Reports, 2020)
Germ cell tumors are the most common testicular tumors, with seminomas the most frequently encountered type. Seminoma with atypical features is an intermediate entity between classical seminoma and embryonal carcinoma and presents with larger tumor size, necrosis, and marked proliferation. We report such a case of seminoma with atypical features in a 38-year-old male who presented with gradually progressive left-sided testicular mass. A computed tomography scan revealed a heterogeneously enhancing mass with cystic areas. Orchidectomy was done and histopathological examination revealed replacement of entire testis with tumor showing large areas of necrosis with a high Ki-67 index. Multiple sections examined showed only two small foci resembling embryonal carcinoma which was negative for CD 30. Hence, a diagnosis of seminoma with atypical features was given and the patient kept under follow-up.